Predicting light-induced stomatal movements based on the redox state of plastoquinone: theory and validation - Kromdijk, Johannes (Photosynth Res, 2019)
Prediction of stomatal conductance is a key element to relate and scale up leaf-level gas exchange processes to canopy, ecosystem and land surface models. The empirical models that are typically employed for this purpose are simple and elegant formulations which relate stomatal conductance on a leaf area basis to the net rate of CO(2) assimilation, humidity and CO(2) concentration. Although light intensity is not directly modelled as a stomatal opening cue, it is well-known that stomata respond strongly to light. One response mode depends specifically on the blue-light part of the light spectrum, whereas the quantitative or ‘red’ light response is less spectrally defined and relies more on the quantity of incident light. Here, we present a modification of an empirical stomatal conductance model which explicitly accounts for the stomatal red-light response, based on a mesophyll-derived signal putatively initiated by the chloroplastic plastoquinone redox state. The modified model showed similar prediction accuracy compared to models using a relationship between stomatal conductance and net assimilation rate. However, fitted parameter values with the modified model varied much less across different measurement conditions, lessening the need for frequent re-parameterization to different conditions required of the current model. We also present a simple and easy to parameterize extension to the widely used Farquhar–Von Caemmerer–Berry photosynthesis model to facilitate coupling with the modified stomatal conductance model, which should enable use of the new stomatal conductance model to simulate ecosystem water vapour exchange in terrestrial biosphere models. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11120-019-00632-x) contains supplementary material, which is available to authorized users.